Pelatihan Pembuatan Kukis Ubi Jalar Ungu bagi Ibu-Ibu PKK di Kecamatan Binakal Kabupaten Bondowoso - Brilliantina, Aulia; Hadi Prasetyo, Frengky Hermawan; Prajna, Deyla (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Bondowoso is one of the regions in East Java with considerable potential for purple sweet potato production. However, its utilization remains limited to direct consumption or simple processed products. Through this community service program, training was provided to local women on producing cookies made from purple sweet potatoes as an alternative food product with nutritional and economic value. The methods included socialization, demonstration, and hands-on practice. The results showed that participants were enthusiastic, capable of applying the production techniques properly, and motivated to develop the product as a home-based business. This activity is expected to enhance skills, foster economic independence, and support local food diversification based on regional potential.